Pengaruh Lama Waktu Biofermentasi Chromolaena odorata dengan Sumber Karbon Gula Lontar Cair Terhadap Konsentrasi pH, VFA Total, NH3 dan Produksi Gas Metan Secara in vitro - Tamara Petan; Gustaf Oematan; Twen O Dami Dato; Gusti Ayu Y. Lestari (Yayasan Sumber Daya Manusia Cerdas, 2023)
The purpose of this study was to determine the effect of Chromolaena odorata biofermentation time with liquid palm sugar carbon source on pH concentration, total VFA, NH3 and methane gas production in vitro. The method used in this research is an experimental method using a completely randomized design (CRD) with 4 treatments and 4 replicates. The treatments were LB21: 21 days of biofermentation as control, LB14: 14 days of biofermentation, LB7: 7 days of biofermentation, LB0: 0 days of biofermentation. The observed variables were pH, total VFA, NH3, and methane gas production. The results of statistical analysis showed that Chromolaena odorata biofermentation with liquid palm sugar carbon source had a significant effect (P<0.05) on pH and NH3 concentrations while total VFA and methane gas production had no significant effect (P>0.05). It is concluded that the length of biofermentation time affects pH and NH3 while not affecting total VFA and methane gas production. Biofermentation time of 14 days gave the best pH value while 7 days gave the best NH3.